BIOPLÁSTICO OBTIDO DE BLENDAS DE CELULOSE E LÁTEX - SELMA RODRIGUES COSTA (2022)
Bioplastics developed from natural resources present themselves as a viable substitute for non-renewable polymers because they are biodegradable, with low cost and toxicity, therefore, the objective of this study was to evaluate the potential use of cellulose combined with natural latex in the production of bioplastic using the species of Camalote (Eichhornia crassipes) and Taboa (Typha domingensis). In the preparation process, the species were dried and crushed. Cellulose extraction was performed by dissolving the product in sodium hydroxide solution. For bleaching, the fibers were subjected to a solution of sodium hypochlorite, acetic acid and sodium hydroxide. The product was filtered, washed, dried and macerated. The powder was mixed with the plasticizers, deposited in petri dishes and dried. Prototypes were obtained that showed homogeneity, absence of bubbles, without evidence of macroscopic cracks and without formation of agglomerates of undissolved particles. It is concluded that the amount of cellulose and latex that varied in obtaining the prototypes was not significant to sustain a difference in the tensile strength and thermal degradation of the prototypes, although it was possible to develop a homogeneous material with good physical properties, which could be applied in the conventional packaging industry, where a resistant and malleable product is required.